North American Clovis Point Form and Performance III: An Experimental Assessment of Knife Cutting Efficiency. (3rd July 2022) - Mika, Anna; Buchanan, Briggs; Walker, Robert; Key, Alastair; Story, Brett; Bebber, Michelle; Eren, Metin I.
ABSTRACT: This study is an experimental assessment of Clovis knife use. This work is the third contribution in a series of experiments aimed at shedding light on the functional performance of distinct Clovis "point" forms. Here, we used seven replica Clovis point forms, representing the average and extremes of observed Clovis form, in two cutting tasks: rope cutting and clay cutting. Statistical comparison of cutting time, our measure of cutting efficiency, indicated differences among the knife forms in both tasks. These results, especially when considered with previous penetration and durability studies, are largely consistent with the hypothesis that selection of functional attributes contributed to Clovis point variability and evolution across North America. We also show that better knives serve as poorer points, and vice versa, but better knives are more durable than poorer knives. We conclude with discussion of knife use, allometry, and knife use in other time periods.